Model predicted optimization of experimental set-up and process conditions for microwave-assisted synthesis of silver nanowires - Sonawane, Jayesh R.; Kulkarni, Amol A. (Chemical Engineering Journal, 2024)
This work presents simulations led optimization of choice of a reactor for an experimental set-up for the continuous production of silver nanowires with certain constraints in terms of yield, reaction time, and dimensions of nanowires. The choice of reactors based on the simulations of reaction kinetics for nucleation and growth phases of driving the optimization of an experimental set-up and subsequent optimization of process conditions to maximize the yield of nanowires of desired dimensions. The optimized reactor configuration is dictated by the reaction kinetics and using a microwave in continuous mode becomes unavoidable. This makes the approach highly reproducible as well as scalable. The integration of conventional and microwave heating is simulated and subsequently optimized experimentally to attain a significant increase in nanowire yield under steady-state conditions with less than 15 min of residence time. The precise control over the rate in different reactor configurations governing nucleation, accelerated growth followed by slow growth to complete the conversion of precursor enables higher selectivity of nanowires with controllable dimensions resulting in 100 gm production per day using simple set-up. We systematically examined key reaction parameters, including the concentration of metal ions, residence time, and different reactor configurations. Our approach successfully yielded AgNWs with 40-60 nm diameter and 15 mu m length. The cost associated with this process for synthesizing AgNWs is less than 10\$ per gram. This study highlights the potential of continuous, high-throughput processes for controlling nanowire size and yield through advanced reactor engineering.
Keywords: Continuous synthesis; Microwave; Reactor design; Silver Nanowires